How do spatial and environmental factors shape the structure of a coastal macrobenthic community and meroplanktonic larvae cohort? Evidence from Daya Bay. (August 2020) - Rao, Yiyong; Cai, Lizhe; Chen, Bingwen; Chen, Xinwei; Zheng, Lianming; Lin, Senjie
Abstract: We examined the relative importance of spatial processes (dispersal-related) and environmental processes (environmental selection-related) in community structure for macrobenthos (including juveniles and adults) and meroplanktonic larvae in the subtidal areas of Daya Bay, China. We found that both macrobenthos and meroplanktonic larvae showed similar spatial patterns, both following the distance-decay relationship. The results of variation partitioning analysis (VPA) showed the roles of both spatial and environmental factors in governing the assembly of both communities, although both explained only a small (slightly larger for spatial factor) fraction of the community variation. We also found that macrobenthos were more affected by spatial processes than meroplanktonic larvae. In addition, we highlight that the mechanisms determining community structure change according to the spatial extent considered. Highlights: Both macrobenthos and meroplanktonic larvae showed similar spatial patterns and followed the distance-decay relationship. The assembly of macrobenthos and meroplanktonic larvae was governed by both spatial and environmental factors. Macrobenthos were more affected by spatial processes than meroplanktonic larvae.